Assessing the technological trajectory of 5G-V2X autonomous driving inventions: Use of patent analysis - Su, Yu-Shan; Huang, Hsini; Daim, Tugrul; Chien, Pan-Wei; Peng, Ru-Ling; Akgul, Arzu Karaman (ELSEVIER SCIENCE INC, 2023)
Cars and the transportation industry are undergoing a radical transformation. In the past, cars were independent means of transportation, and motor vehicles could not communicate with each other or the nearby environment. Nowadays, the Internet of Vehicles (IoV) technology and autonomous driving vehicles are gradually becoming a reality. Thanks to its high data throughput, fast data transmission rate, and low latency, 5G mobile communication technology lies at the heart of this technological transformation. The Internet of Vehicles service promoted by the 5G Automotive Association (5GAA) is recognized as a market-leading technological development strategy. In this service, which integrates 5G mobile data with the Internet of Vehicles, Connected Autonomous Vehicles (CAV) will play a key role in the next generation of Cooperative Intelligent Transport Systems (C-ITS).In this paper, we apply a series of patent analyses to investigate the global 5G-V2X (vehicle-to-everything) patent distribution, compare patents of the major technology assignees, and assess the technological growth curves for eight different 5G-V2X applications in the field of autonomous driving. The results of this study indicate that R&D on 5G-V2X and autonomous driving applications and technologies began growing in 2018, and development has remained at a high level, with the United States, Korea, and China as the three leading patented technology-holders. Analysis of the patent holding share of patent right-holding companies reveals that Qualcomm, LG, and Ericsson have relatively large shares of patented technology in the field of autonomous driving applications. The network analysis of IPC 3-digit symbols indicates that H04W, H04B, G08G, and H04L are important relevant technology areas. Our findings can contribute valuable information concerning 5G-V2X autonomous driving applications to government, industry, and academia.
Keywords: Patent analysis; Fifth generation; 5G mobile communication technology; Cellular vehicle-to-everything communication; (C-V2X); Connected and autonomous vehicle (CAV); Growth curve model; FORECASTING EMERGING TECHNOLOGIES; SCIENCE-AND-TECHNOLOGY; NETWORK ANALYSIS; VEHICLES; INDUSTRY; DRIVERS; FIELD; TOOL; Business & Economics; Public Administration